PENGARUH DRILL MENGOPER BOLA TERHADAP AKURASI PASSING SEPAKBOLA PADA SEKOLAH SEPAK BOLA PATRIOT MUDA U-15 KUOK - Wahyu Jelsal; Slamet '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is the lack of accuracy of passing ability to pass the ball at short passing, long passing, through passing ball and normal passing / wall passing 1-2 at the Patriot Muda Football School U-15 Kuok. Based on these problems the researcher provide drill training passing the ball. This research goals to determine whether there is influence of drill training passing ball to the accuracy of passing at Patriot Muda U-15 Kuok Football School. So when passing and receiving the ball will get good passing result. This form of research is experimental research, with a population of Patriot Muda U-15 Kuok football school's players. The data in this research is the whole population which is in total 16 peoples. Instruments performed in this research is a short passing accuracy test, which aims to measure the general ability in football. After that, the data were processed by statistics, to test the normality by the lilifors test at a significant level of α (0.05). Hypothesis proposed is the effect of drill training passing to the accuracy of football passing. Based on statistical data analysis, there is an average pre-test of 5.06 and average post-test of 6.13, then the data is normal with an increase of 1.07. Based on t test analysis result Tcount equal to 4.08 and Ttable 1,753, mean Tcount> Ttable. So that, there is a significant effect of drill passing the ball to passing accuracy at Patriot Muda U-15 Kuok Football School.Key Words : Drill Passing The Ball, Passing Accuracy.